Measurements of sediment pickup rate over dune-covered bed - Emadzadeh, Adel (2015)
Laboratory experiments were conducted to measure sediment pickup rate over two-dimensional fixed dunes. Measurements were performed over both stoss and lee sides of the dune with sediments of D 50 = 0.23, 0.44 and 0.86 mm. Flow velocity and turbulence were also measured by using an acoustic Doppler velocimeter. By analysing the experimental data, an empirical sediment pickup function based on depth-averaged flow parameters was proposed to estimate the pickup rate over the dune.